Tikal : a handbook of the ancient maya ruins, with a guide map. - Coe, William R. (University of Pensilvania, 1967)
An introduction. The visitor at Tikal. The discovery of Tikal. The ruins. The car ved monuments. The growth and decline of Tikal. Appendix. Selected bibliography. Acknowledgments.